OpenSHMEM and related technologies : enhancing OpenSHMEM for hybrid environments : third workshop, OpenSHMEM 2016, Baltimore, MD, USA, August 2-4, 2016, Revised selected papers /: enhancing OpenSHMEM for hybrid environments : third workshop, OpenSHMEM 2016, Baltimore, MD, USA, August 2-4, 2016, Revised selected papers. (2016) - Unknown
No abstract available